Elevated Expression of Vacuolar Nickel Transporter Gene IREG2 Is Associated With Reduced Root-to-Shoot Nickel Translocation in Noccaea japonica - Nishida, Sho; Tanikawa, Ryoji; Ishida, Shota; Yoshida, Junko; Mizuno, Takafumi; Nakanishi, Hiromi; Furuta, Naoki (Frontiers in Plant Science, 2020)
A number of metal hyperaccumulator plants, including nickel (Ni) hyperaccumulators, have been identified in the genus Noccaea. The ability to accumulate Ni in shoots varies widely among species and ecotypes in this genus; however, little is known about the molecular mechanisms underlying this intra- and inter-specific variation. Here, in hydroponic culture, we compared Ni accumulation patterns between N. japonica, which originated in Ni-enriched serpentine soils in Mt. Yubari (Hokkaido, Japan), and N. caerulescens ecotype Ganges, which originated in zinc/lead-mine soils in Southern France. Both Noccaea species showed extremely high Ni tolerance compared with that of the non-accumulator A. thaliana. But, following treatment with 200 µM Ni, N. caerulescens showed leaf chlorosis, whereas N. japonica did not show any stress symptoms. Shoot Ni concentration was higher in N. caerulescens than in N. japonica; this difference was due to higher efficiency of root-to-shoot Ni translocation in N. caerulescens than N. japonica. It is known that the vacuole Ni transporter IREG2 suppresses Ni translocation from roots to shoots by sequestering Ni in the root vacuoles. The expression level of the IREG2 gene in the roots of N. japonica was 10-fold that in the roots of N. caerulescens. Moreover, the copy number of IREG2 per genome was higher in N. japonica than in N. caerulescens, suggesting that IREG2 expression is elevated by gene multiplication in N. japonica. The heterologous expression of IREG2 of N. japonica and N. caerulescens in yeast and A. thaliana confirmed that both IREG2 genes encode functional vacuole Ni transporters. Taking these results together, we hypothesize that the elevation of IREG2 expression by gene multiplication causes the lower root-to-shoot Ni translocation in N. japonica.